Malignant melanoma with pituitary metastasis: A case report and literature review - Li, Xiaoling; Jiang, Wenhui; Tang, Xiaohui; Chen, Meiying; Deng, Wenhua; Wang, Yunyu; Wang, Xingfu (Frontiers in Endocrinology, 2025)
PurposePituitary metastasis of malignant melanoma (MM) is rare. This study aimed to explore its diagnostic features using a multimodal approach and retrospectively analyzed previously reported cases to summarize its pathogenesis and diagnostic challenges.MethodsWe screened all published case reports and case series on pituitary metastatic MM using PubMed, focusing on cases with detailed clinical data, imaging features, pathological examination, and molecular test results. A total of 24 cases of MM with pituitary metastasis, including our case, were retrospectively analyzed. Additionally, the index patient underwent histopathological, immunohistochemical (S100, SOX10, Melan-A, HMB-45, BRAF V600E), and BRAF V600E PCR analyses.ResultsThis case involved a 65-year-old female patient whose pathological examination revealed tumor cells with epithelioid and spindle cell features. Immunohistochemical analysis showed diffuse positivity for S-100, vimentin, and BRAF V600E, with focal positivity for Melan-A and HMB-45. The Ki-67 proliferation index was approximately 15%. Molecular testing confirmed BRAF V600E mutation. The patient died 12 months postoperatively. Our literature review indicated that MM with pituitary metastasis demonstrates male predominance, a median onset age of 62 years, a frequent association with BRAF V600E mutation, and a median survival time of 12 months.ConclusionDiagnosing MM with pituitary metastasis requires integrating detailed clinical history, imaging features, pathological examination, and molecular testing. Our findings highlight the importance of a comprehensive diagnostic approach with multidisciplinary collaboration when managing atypical pituitary masses, along with detailed investigation of a patient’s previous tumor history, to improve diagnostic accuracy and patient outcomes.